Potential Anti-obesogenic Effects of Ginkgo biloba Observed in Epididymal White Adipose Tissue of Obese Rats - Hirata, Bruna K. S.; Cruz, Maysa M.; de Sá, Roberta D. C. C.; Farias, Talita S. M.; Machado, Meira M. F.; Bueno, Allain A.; Alonso-Vale, Maria Isabel C.; Telles, Monica M. (Frontiers in Endocrinology, 2019)
Exacerbated expansion of adipose tissue seen in diet-induced obesity leads to endocrine dysfunction and disturbance in adipokine secretion, with such abnormal profile positively associated with type 2 diabetes and other mild chronic inflammatory conditions. Ginkgo biloba extract (GbE), a mixture of polyphenols with antioxidant properties, has been recently investigated in a variety of experimental models of endocrine dysfunction, with several potentially beneficial effects identified, including improvement in insulin sensitivity in obese rats, and reduction of weight gain in ovariectomy-induced obesity and diet-induced obesity. The aim of this study was to investigate in high fat diet-induced obese male rats the effects of GbE supplementation for two weeks on adipocyte volume and adipose tissue lipid accumulation. GbE supplementation was effective in reducing energy intake in obese rats compared to the saline-treated placebo group. Epididymal adipocyte volume was reduced in GbE-supplemented rats, as were epididymal [1-14C]-acetate incorporation into fatty acids, perilipin (Plin 1) and fatty acid synthase (Fasn) mRNA, and FAS protein levels. Adipocyte hypertrophy in obesity is associated with insulin resistance, and in the present study we observed a reduction in the adipocyte volume of GbE-supplemented obese rats to dimensions equivalent to adipocytes from non-obese rats. GbE supplementation significantly reduced acetate accumulation and tended to reduce [3H]-oleate incorporation, into epididymal adipose tissue, suggesting a potentially anti-obesogenic effect in longer term therapies. Further studies that investigate the effects of GbE supplementation in other experimental models are required to fully elucidate its suggested beneficial effects on mild chronic inflammatory conditions.